Formulasi sabun mandi esensial minyak nilam dengan pewarna kopigmentasi biji kesumba keling (Bixa orellana L.) dengan angkak merah - Indriana , Meutia; Sari, Nurmala; Julianty , Siti Muliani; Muzakkir, Muzakkir; Febriani , Yessi; Nurrahman, Taufik; Salman, Salman (Journal of Pharmaceutical and Sciences, 2024)
Background; The skin is the outermost layer of the body that serves as a protective barrier against exposure to sunlight and is also where sweat is produced. Sweat can make the skin appear dull and sticky. Soap is a cosmetic product that is used for body cleansing. Annatto and red mold rice are used as natural colorants formulated in soap preparations, where the color produced by annatto and red mold rice is not stable. Therefore, a copigmentation method is needed to stabilize the colorant annatto with red mold rice. Method; This research use an experimental approach that initially involves the extraction of annatto seeds and red mold rice using 96% ethanol. Subsequently, the extracted compounds are formulated into soap preparations with variations in ratios of 1:1, 1:2, 2:1, and 2:2. To evaluate the quality of the soap preparations, various tests have been conducted, including homogeneity testing, pH testing, foam height testing, water content testing, and irritation testing. Result; The results showed that the copigmentation of annatto seeds with red mold rice in the form of ethanol extract could be formulated into a soap dosage form at a ratio of 2:1 (F4) is the best preparation, is a homogeneous preparation, has a pH of 9.4 , has a foam height of 8.3 cm, has a water content of 6.25%. All copigmented soap with ethanol extract of annatto seeds with red mold rice does not irritate the skin of the hands.